School mathematics and teaching authorship in Brazilian curriculum production (1929-2019) - Júlio César Augusto Valle (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The purpose of this text is to present an institutional research and discuss the partial results of its development. The proposal is situated in the context of the "Mathematics in the curriculum of Basic Education, its epistemologies and policies", which aims to map and analyze the curricular proposals and/or the prescribed curriculum in Brazil, from 1929 to 2019, so that it is possible to understand how the epistemology of mathematics supported each movement, as well as its implications for the teaching of the discipline in each historical period. Furthermore, it seeks to understand and discuss the production/formulation contexts of each curricular proposal in terms of showing whether there was teacher participation/authorship in its elaboration. The preliminary results achieved by the investigation are part of the search to subsidize a critical look at the field of curriculum in its interface with Mathematics Education.